2021
DOI: 10.1071/rd20247
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of the endocannabinoid N-arachidonoylethanolamine in the follicular fluid of women with endometriosis: the role of M1 polarised macrophages

Abstract: Although N-arachidonoylethanolamine (AEA; also known as anandamide) is present in human follicular fluid (FF), its regulation remains unknown. Therefore, the aims of the present study were to: (1) investigate the relationships between FF AEA concentrations in women undergoing assisted reproductive technology and their age, body mass index, ART characteristics and fertility treatment outcomes; and (2) assess how different inflammatory patterns may trigger AEA production by human granulosa cells (hGCs). FF AEA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To date, little is known about the role of ECS in the pathogenesis of endometriosis; however, cannabinoids may contribute to the inflammation closely related to endometriosis [ 92 ]. It has been demonstrated that M1 macrophages stimulated AEA production by granular cells, which may explain the increased level of AEA in the follicular fluid in the course of endometriosis [ 93 ]. Moreover, similarly to EP, increased levels of systemic AEA were shown along with decreased expression of CB1 in the secretory phase as compared to the control.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…To date, little is known about the role of ECS in the pathogenesis of endometriosis; however, cannabinoids may contribute to the inflammation closely related to endometriosis [ 92 ]. It has been demonstrated that M1 macrophages stimulated AEA production by granular cells, which may explain the increased level of AEA in the follicular fluid in the course of endometriosis [ 93 ]. Moreover, similarly to EP, increased levels of systemic AEA were shown along with decreased expression of CB1 in the secretory phase as compared to the control.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…The differentiation protocol used in this study was based on the one previously published by our research group. We initiated THP-1 differentiation by exposing the cells to PMA (25 ng/mL) for 48 h, followed by a 24 h resting period [18]. Differentiation of monocytes into resting M0 was confirmed by observation that macrophage-like cells adhered to tissue culture flask, adopting a stellate 2 Effects conditioned media obtained from culture of M1 and M2 macrophages in hGCs and COV434 cells viability.…”
Section: Discussionmentioning
confidence: 99%
“…THP-1-derived macrophages were obtained following a previous procedure described by Fonseca et al [ 18 ], with some modifications. Firstly, THP-1 cells were seeded at a density of 5.0 × 10 5 cells/well in a 24-well plate and stimulated with PMA (25 ng/mL) for 48 h. After PMA exposure, the medium was discarded and the cells were washed with PBS, followed by a further incubation in fresh medium for 24 h as a resting period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation